Teaching and learning in higher education : the context of being, interculturality and new knowledge systems - Kumar, Margaret; Welikala, Thushari (Emerald Publishing Limited, 2021)
This book approaches notions of Being, Interculturality and New Knowledge Systems, through a team of expert contributors who share their evidence-based knowledge constructed within diverse geo-political borders. It explores the disjuncture, assumptions, and beliefs associated with the concepts of Being, Interculturality and New Knowledge Systems, to reveal avenues for reconsidering untapped bodies of knowledge and how they are being positioned within teaching, learning and researching in higher education. This volume is built on conceptual and theoretical insights from a range of different disciplines, and explores the social-historical underpinnings of Being, 'becoming' and 'to be'. The book deepens understanding on Indigeneity and how culturally diverse, environmentally sustaining, interculturally and transnationally unprecedented, alternative knowledges have long been disregarded as globally irrelevant and intellectually insignificant. It attempts to address the missing connections between what is recognised as 'global knowledge' and the locally situated, underrepresented knowledges that are being constructed within diverse types of peripheries across contexts. This edited volume is essential reading for academics, researchers, policy-makers and students in higher education.